Implementing Software Quality Assurance (SQA) in UiTM Pahang: the preliminary study of formal methods in software development life cycle / Noraini Mohamed, Mahfudzah Othman and Nursyahidah Alias - Mohamed, Noraini; Othman, Mahfudzah; Alias, Nursyahidah (2008)
This paper is aimed to study the method of Software Quality Assurance (SQA) that can be implemented in Universiti Teknologi MARA (UiTM) Pahang. Software quality as defined by Institute of Electronics and Electrical Engineers (IEEE) is the degree to which a system component or process meets specified requirements and user needs or expectations. Whereas, Software Quality Assurance (SQA) is a planned and systematic pattern of all actions necessary to provide adequate confidence that an item or product conforms to established technical requirements. [n this study, we will investigate the use of formal methods that is integrated in software project life cycle development to ensure the quality assurance of the software. Focus is given to a number of methods only, which are the B Method, SDL, VDM, Z Language and Cleanroom Software Development. This paper will compare these techniques to study the use of formal methods in the Software Development Life Cycle (SDLC).